A Study on the Potential of Cost and Energy - A Survey at Playford Building, University of South Australia - Ramli, Junid; Y., Nor Imrah; A. R., Jeeferie; Mohamad Mazwan, Mahat (Faculty Mechanical Engineering, UMP, 2011)
This report summarizes a study on energy consumption of a building, and offers recommendations to reduce the cost of energy usage. Playford building, of the University of South Australia, has been chosen as the study example for completing this survey. The study uses three phases of workflow: an audit of historical energy consumption data, a screening survey, and a detailed investigation and analysis of the building itself. One year of past data have been retrieved and analyzed. Causes of energy wastage and areas with potential for energy savings have been identified by walk-through survey across two levels of the building, chosen to represent the entire building. Possible ways of reducing energy consumption have been recommended. An estimation of the energy savings, following implementation of the recommendations, has been calculated including costs that would be incurred. It was found that for six recommendations, an estimated 20.4% of energy could be saved relative to present consumption. An amount of $AUD 11264.5 per annum could be saved by the university on utility bills for electrical appliances based on an average price of electricity of 0.114592 c/kWh.